Constraining Lateglacial and early Holocene environmental changes in Wales and Germany using tephrochronology. - Gwydion Jones (2018)
Evidence for the abrupt Lateglacial climatic changes is observed in many palaeorecords, however the mechanisms and triggers behind these changes are still unknown. The preferred hypothesis is thought to be linked with the disruption in the North Atlantic Ocean circulation, therefore palaeoclimatic records from maritime regions are needed to investigate the impact of these abrupt changes. The Greenland ice-core records provide high-resolution evidence of these changes, in addition to many marine and terrestrial records throughout the North Atlantic. However, there is a lack of studies on sites in the south western coastal regions of the British Isles that are well-constrained by robust chronologies. The latter, in particular, hampers our understanding of the mechanisms driving the rapid climate changes of the Lateglacial due to the difficulties of integrating and comparing the climatic response in diverse proxy records. In an attempt to resolve these challenges tephrochronology was employed as a precise correlation technique to investigate three Lateglacial sequences from Wales (Llyn Llech Owain, Cors Carmel and Pant- y-Llyn). An additional site from north Germany (Lake Hämelsee) was also included in this study and chosen due to its potential to preserve tephra from more than one volcanic region and develop a European tephra framework or stratotype for the Lateglacial.Twenty-one tephra deposits were identified across the network of sites. Twelve deposits have been correlated to known eruptions and in most cases have extended the geographical distribution of their respective ash dispersal. Icelandic tephra deposits of Lateglacial age such as the Askja-S Tephra have been discovered in Welsh sites for the first time highlighting the potential of employing tephrochronology more widely in areas such as Wales, south England and perhaps France. Furthermore, three non-Icelandic deposits, that originate from the Cascade region, Alaska and Italy, have been discovered in the Llyn Llech Owain record, allowing the synchronisation of records across a trans-continental scale. The Askja-S Tephra, Ulmener Maar Tephra and Vedde Ash are added to the tephrostartigraphy of the Hämelsee record highlighting its importance as a key site within the European tephra lattice.Nine of the discovered tephra deposits in Llyn Llech Owain and Lake Hämelsee have not been correlated and may represent new eruptions and potentially new tephra isochrons for future studies. Tephra results are supplemented by multi-proxy palaeoenvironmental reconstructions including lithostratigraphic data, sediment geochemistry, palaeoecology and radiocarbon dating where possible.In addition to providing fix-points for potential age-models, the discovered tephra deposits allow the study sites to be independently synchronised with other tephra bearing sites. This allows investigations to be made between sites to constrain any leads or lags in the environmental response to climate change and in turn help determine the mechanisms that cause these abrupt climate changes.